Developing a Maximal Leg Power Device Using Ultrasonic Sensor with Liquid Crystal Display. - Rusdiana, Agus; Budiana, Dian (Pertanika Journal of Social Sciences & Humanities)
Auto technology is a new breakthrough in developing devices related to sports enhancement. Therefore, the purpose of this study was to develop a device based on ultrasonic sensor using a liquid crystal display to maximise leg power. The components of the new device are a microcontroller ATMEGA-328, liquid crystal display and HC-SR04 ultrasonic sensor. The study was conducted in the laboratory of sport science, faculty of sport and health education, Indonesia University of Education. Ten students from Sport Science study program were recruited as samples. A prototype of maximal leg power measurement device was invented and results showed that there were no significant differences between auto and manual testing. However, the device can be used to determine maximal leg power more accurately, easily and effectively.